Evaluation of nurses' attitudes and behaviors regarding narcotic drug safety and addiction: a descriptive cross-sectional study - Ayten Kaya; Zila Özlem Kirbaş; Suhule Tepe Medin (BMC, 2024)
Abstract Background By evaluating nurses' attitudes and behaviors regarding narcotic drug safety and addiction, effective strategies need to be developed for combating addiction in healthcare institutions. This study, aimed at providing an insight into patient and staff safety issues through the formulation of health policies, aimed to evaluate nurses' attitudes and behaviors regarding narcotic drug safety and addiction. Methods The study was conducted in a descriptive cross-sectional design. It was carried out with 191 nurses in a public hospital between March 2023 and August 2023. Data were collected through face-to-face interviews, gathering socio-demographic information and utilizing the Addictive Substance Attitude Scale. The data were analyzed using independent sample t-tests, one-way ANOVA tests, and regression analysis (P < .001 and p < .05). Results The average age of the participants was determined to be 36.58 ± 8.40. It was reported by 85.3% of nurses that narcotic drug follow-ups in their units were conducted according to procedures. In the study, it was found that 63.9% of nurses did not know the procedure to be followed towards a healthcare professional identified as a narcotic substance addict. The total mean score of the Addictive Substance Attitude Scale of nurses participating in the study was 74.27 ± 14.70. A significant difference was found between the total scores of the scale and the level of education of nurses, the follow-up status of the drugs in the unit where they work, their status of receiving narcotic drug addiction training, and their routine use of the half-dose drug disposal form (p < .05). Conclusions The findings of this study underscore the importance of evaluating nurses' attitudes and behaviors regarding narcotic drug safety and addiction. These results indicate the need for nursing administrators, particularly in terms of patient and staff safety, to adopt more effective policies and strategies.